Preconditioning and Engineering Strategies for Improving the Efficacy of Mesenchymal Stem Cell-Derived Exosomes in Cell-Free Therapy - Shenyuan Chen; Fengtian Sun; Hui Qian; Wenrong Xu; Jiajia Jiang (Hindawi Limited, 2022)
Mesenchymal stem cells (MSCs) have been widely applied to regenerative medicine owing to their multiple differentiation, self-renewal, and immunomodulatory abilities. Exosomes are cell-secreted natural nanovesicles and thought to be mediators of intercellular communication and material transport. The therapeutic potential of MSCs can be largely attributed to MSC-derived exosomes (MSC-exosomes). Emerging evidence suggests that the therapeutic efficacy of MSC-exosomes is highly dependent on the status of MSCs, and optimization of the extracellular environment affects the exosomal content. Pretreatment methods including three-dimensional cultures, hypoxia, and other biochemical cues have been shown to potentially enhance the biological activity of MSC-exosomes while maintaining or enhancing their production. On the other hand, engineering means to enhance the desired function of MSC-exosomes has been rapidly gaining attention. In particular, biologically active molecule encapsulation and membrane modification can alter or enhance biological functions and targeting of MSC-exosomes. In this review, we summarize two possible strategies to improve the therapeutic activity of MSC-exosomes: preconditioning approaches and engineering exosomes. We also explore the underlying mechanisms of different strategies and discuss their advantages and limitations of the upcoming clinical applications.